The effectiveness of school closures and other pre-lockdown COVID-19 mitigation strategies in Argentina, Italy, and South Korea - Guido Neidhöfer; Claudio Neidhöfer (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
The rapid spread of COVID-19 forced policy-makers to swiftly find solutions to reduce infection rates and keep mortality as low as possible. Empirical analyses on the effectiveness of control measures are hereby of primary importance. School closures were among the earliest measures enacted by the governments of most countries. However, while schools are now reopening in many countries, the impact of school closures on the course of the epidemic is still an open question. Adopting parametric and non-parametric synthetic control methods we estimate the effectiveness of pro-active school closures, and other early social distancing interventions, in three countries that reacted relatively early during the course of the pandemic. Our findings suggest that these interventions were effective at reducing the mortality rate of COVID-19, especially when enacted early.
Keywords: I18; J18; 330; COVID-19; policy evaluation; school closures; mitigation strategies